Health-motivated taxes on red and processed meat: A modelling study on optimal tax levels and associated health impacts - Springmann, Marco; Mason-D'Croz, Daniel; Robinson, Sherman; Wiebe, Keith D.; Godfray, H. Charles J.; Rayner, Mike; Scarborough, Peter (Public Library of Science, 2018)
The consumption of red and processed meat has been associated with increased mortality from chronic diseases, and as a result, it has been classified by the World Health Organization as carcinogenic (processed meat) and probably carcinogenic (red meat) to humans. One policy response is to regulate red and processed meat consumption similar to other carcinogens and foods of public health concerns. Here we describe a market-based approach of taxing red and processed meat according to its health impacts.